Apoyo social y resiliencia con calidad de vida en participantes del Programa Adulto Mayor de centros de salud en un distrito de Chiclayo, 2017 - Soza Carrillo, Fiorella Eliana (2020)
The main objective of the research was, to determine the relationship between social support and resilience with quality of life in participants of the Elderly Adults Program of Health Centres in a District of Chiclayo, and as specific objectives, to identify the frequency by levels of social support and resilience, as well as, levels of quality of life by dimensions, and the relationship between the social support and resilience with quality of life by dimensions 82 people of both sexes, the technique used was the survey through the Social Support Questionnaire of Moss (1991), adapted by Villalobos (2014) in Chiclayo, the Resilience Scale of Wagnild and Young (1993), adapted in Peru by Castilla et al. (2016) in Lima, and the Quality of Life Questionnaire (WHOQOL-BREF), adapted in Chile by Espinoza et al (2011); obtaining as a result that social support and resilience are related to quality of life in a high way (0.632).